А Crack, a Gulf, an Abyss… - Bagina, Elena (project baikal, 2015)
Our world is on the eve of drastic changes and transformations. The future of the architectural profession depends on how clearly the professional society can formulate the actual state of architecture. A great number of constructions are being built, and cities acquire a brand new image. At the same time, the situation in architecture and town planning is critical. Contemporary architecture has become a sort of branch of the industrial design with its semantic potential minimized to purity, convenience and economical efficiency. The dream of avant gardists of the early XXth century has come true. The old has been almost completely destroyed. The society fails to understand the sense of architecture of the past, including the XXth century. Such situation leads to unconscious barbarism towards historical heritage.